A multiscale assessment protocol to quantify effects of restoration works on alluvial vegetation communities. (July 2018) - Staentzel, Cybill; Beisel, Jean-Nicolas; Gallet, Sébastien; Hardion, Laurent; Barillier, Agnès; Combroux, Isabelle
Highlights: We developed a protocol to quantify multiscale changes in vegetation dynamics. The protocol was applied on a field study in large river, using a BACI design. Restoration works provided a patchy habitat mosaic. This approach can be extended to other programs in applied ecology. Abstract: Vegetation mapping is a legal obligation in environmental monitoring prompting the need for easy-to-read methods of quantifying changes in vegetation dynamics. Transition matrix modelling provides an alternative approach to qualitative assessment promoting quantification for revealing current complex changes effects on the trajectory of ecosystems. Transition matrix models (TMMs) and two newly developed metrics, the pixel change (PCI) and zonal change (ZCI) indices, were combined into a methodological scheme that provides a multiscale assessment protocol. This protocol was applied during a field study along the Old Rhine River in order to assess complex shifts in alluvial vegetation communities in relation to restoration works and natural processes. The restoration works aim to restore lateral mobility through instream flow increase and controlled bank erosion with artificial groynes implementation. Characterisation of spatial and temporal pathways was carried out using a 'before-after control-impact' (BACI) design, and a fuzzy coding approach has shed further light on shifts in aquatic vegetation functional traits. The multiscale assessment protocol highlighted (i) an increase in alluvial habitat types, including habitats of European concern (Natura 2000), and (ii) low time-scale aquatic vegetation recovery. Both ZCI and PCI recorded high values along the restored section with controlled bank erosion, indicating strong ecosystem change. Use of functional traits detected three requirements for the successful establishment of aquatic vegetation in the restored river section, i.e. high degree of flexibility, flow variation tolerance, and fine-sediment adaptability. Subject to the reliability and availability of vegetation mapping, the method opens the possibility of an efficient tool for precisely monitoring alluvial vegetation communities and identifying pathways. It also discriminates event effects, e.g. natural process effects vs. human-induced effects. At full potential, such a protocol may reveal community responses to disturbance during conservation, restoration and management decision-making projects.